Semiotic Analysis of Charless Sanders Pierce Construction of Mental Meaning Breakdown: Analisis Semiotika Charless Sanders Pierce Konstruksi Makna Mental Breakdown - Nursadapu, Dhea Novita; Febriana, Poppy (Indonesian Journal of Innovation Studies, 2023)
This research aims to describe what the meaning of what is stored in the Youtube channel by reviewing about mental break down, which is often also considered negative by most people, especially in Indonesia itself. One episode on the YouTube channel "MARSHED" titled "From Mental breakdown To Be A Champion". The 27th episode of Chanel Marshanda was chosen by researchers because it tells the story of her personal experience when she experienced a mental breakdown. Which researchers say is particularly relevant to this study on the construction of mental breakdown meanings.In this study researchers got meaning based on the triangular element Charles Sanders Pierce, the three main elements referred to as triangle meaning or triangle of meaning. There are three angles, namely signs (signs), objects (objects), and interpretants (interpretants).From the findings of researchers,.there are many symbols that refer to the meaning in the life experience of a mental breakdown sufferer where it is Marshanda himself with the fear experienced. Marshanda also feels discomfort in life where he does not want to meet anyone. He also felt dependence on sedatives. Marshanda had wanted to kill himself before finally finding a way to heal and also how he rose from adversity.